2013
DOI: 10.1038/srep02702
|View full text |Cite
|
Sign up to set email alerts
|

Anti-LRP/LR specific antibody IgG1-iS18 and knock-down of LRP/LR by shRNAs rescue cells from Aβ42 induced cytotoxicity

Abstract: Alzheimer's disease (AD) is characterized by neurofibrillary tangles, senile plaques and neuronal loss. Amyloid beta (Aβ) is proposed to elicit neuronal loss through cell surface receptors. As Aβ shares common binding partners with the 37 kDa/67 kDa laminin receptor (LRP/LR), we investigated whether these proteins interact and the pathological significance of this association. An LRP/LR-Αβ42 interaction was assessed by immunofluorescence microscopy and pull down assays. The cell biological effects were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…The effects of hindering the interaction between β-secretase and LRP/LR would thus have to be examined in detail in future studies, to test for the effects it may have on the other physiological roles in which β-secretase is involved. Cell viability assays, however, have been performed using IgG1-iS18 on HEK293 cells, and no significant reduction in cell viability was observed44, thus suggesting whatever interaction the antibody may be blocking between β-secretase and LRP/LR is not detrimental to the cells.…”
Section: Discussionmentioning
confidence: 98%
“…The effects of hindering the interaction between β-secretase and LRP/LR would thus have to be examined in detail in future studies, to test for the effects it may have on the other physiological roles in which β-secretase is involved. Cell viability assays, however, have been performed using IgG1-iS18 on HEK293 cells, and no significant reduction in cell viability was observed44, thus suggesting whatever interaction the antibody may be blocking between β-secretase and LRP/LR is not detrimental to the cells.…”
Section: Discussionmentioning
confidence: 98%
“…Antibody blockade and shRNA mediated downregulation of LRP/LR was shown to significantly enhance the viability and proliferative potential of cells treated with Aβ 42 26. In this study we aimed to further probe the mechanism underlying the role of LRP/LR in mediating Aβ pathogenesis.…”
mentioning
confidence: 99%
“…Owing to the fact that LRP/LR and Ab share numerous mutual binding partners including PrP c , laminin-1 and heparin sulphate proteoglycans, the possibility of an association between the 37/67 kDa LRP/LR and Ab warranted investigation and Da Costa Dias et al [98], were the first to explore this possibility and report that this association indeed exists and has cell biological effects. The authors demonstrated that LRP/LR co-localises with Ab 42 on the cell surface and co-immunoprecipitation assays revealed that a physical association occurs between the receptor and synthetic Ab 42 peptides.…”
Section: The Role Of Lrp/lr In Admentioning
confidence: 98%